2016
DOI: 10.3389/fphys.2016.00411
|View full text |Cite
|
Sign up to set email alerts
|

Acute High-Intensity Interval Exercise-Induced Redox Signaling Is Associated with Enhanced Insulin Sensitivity in Obese Middle-Aged Men

Abstract: Background: Obesity and aging are associated with increased oxidative stress, activation of stress and mitogen activated protein kinases (SAPK), and the development of insulin resistance and metabolic disease. In contrast, acute exercise also increases oxidative stress and SAPK signaling, yet is reported to enhance insulin sensitivity and reduce the risk of metabolic disease. This study explored this paradox by investigating the effect of a single session of high-intensity interval-exercise (HIIE) on redox sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 51 publications
3
48
1
4
Order By: Relevance
“…Growing evidences suggest that exercise‐induced low‐to‐moderate ROS elevations exerts pivotal role for positive physiological adaptations . Moreover, previous data demonstrated that single HIIE enhances total and enzymatic antioxidant activities after the bout induced by acute oxidative damage . Thus, ROS‐signaling induced by HIIE seems to be controlled by changes in antioxidant system that contributes to exercise adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidences suggest that exercise‐induced low‐to‐moderate ROS elevations exerts pivotal role for positive physiological adaptations . Moreover, previous data demonstrated that single HIIE enhances total and enzymatic antioxidant activities after the bout induced by acute oxidative damage . Thus, ROS‐signaling induced by HIIE seems to be controlled by changes in antioxidant system that contributes to exercise adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…Excess ROS activate stress and mitogen activated protein kinase signaling pathways in insulin sensitive tissues contributing to the development of insulin resistance and type 2 diabetes (Wright et al, 2006; Tiganis, 2011). However, research has also highlighted exercise-induced ROS as a prominent moderator of glycemic control (Ristow et al, 2009; Trewin et al, 2015; Parker et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Exercise-induced oxidative stress and subsequent redox-sensitive protein signaling facilitate many of the health benefits of acute and regular exercise (Ristow et al, 2009; Radak et al, 2013; Trewin et al, 2015; Parker et al, 2016). Furthermore, many of the metabolic health benefits of higher-intensity exercise occur during the delayed exercise recovery period (i.e., the day after exercise), potentially through alterations in redox status (Tyldum et al, 2009; Gabriel et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…All types of leisure time physical activities as well as occupational physical activity were found to be inversely associated with diabetes risk [41, 42]. The beneficial effect of exercise on insulin sensitivity and glycaemic control (by continuous glucose measurement) has also been demonstrated in controlled trials in non-diabetic individuals [43, 44]. Reallocation of 30 min of sedentary time into moderate to vigorous physical activity was associated with a 15% difference in HOMA-defined insulin sensitivity [45].…”
Section: Overview Of Environmental and Lifestyle Factors Increasing Tmentioning
confidence: 99%